Pengaruh Kepercayaan dan Harga Terhadap Loyalitas dengan Kepuasan Sebagai Variabel Intervening: Studi Kasus pada Pasien Klinik Sukaraya Medika Bekasi - Sarmin; Irawan, Andri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine the effect of trust and price on satisfaction, both partially and simultaneously, as well as the effect of trust, price, and satisfaction on loyalty, both partially and simultaneously. Additionally, the study examines the direct and indirect effects of trust and price on loyalty by introducing satisfaction as an intervening variable. This research is associative in nature with a quantitative approach. The population in this study includes all patients who have received treatment at Sukaraya Medika Clinic, with a sample size of 100 respondents calculated using the Purba formula. The sampling technique employed is incidental sampling. The research instrument is a questionnaire using a Likert scale, distributed via Google Forms as well as printed copies. Data validity and reliability were measured through validity and reliability tests, and data analysis was conducted using path analysis with the help of SPSS software. The results of this study indicate that the variables of trust and price have a positive and significant effect on patient satisfaction, both partially and simultaneously. Furthermore, the variables of trust, price, and satisfaction have a positive and significant effect on patient loyalty, both partially and simultaneously. The indirect effects of trust and price on loyalty through satisfaction as an intervening variable are greater than the direct effects of trust and price on loyalty.